EXPLORING THE INTERPLAY BETWEEN LANGUAGE ATTITUDES AND ENGLISH LEARNING MOTIVATION IN AN INDONESIAN INTERNATIONAL SCHOOL - Marhamah Marhamah; Dini Hidayati (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
This study aims to examine students' attitudes toward English and analyze the relationship between language attitudes and motivation to learn English in Indonesian international schools. This is motivated by the increasing role of English as a global lingua franca in education, technology, business, and intercultural communication. Globally, English is spoken by more than 1.5 billion speakers as a first or second language, and is the dominant language in scientific publications, with over 80% of international journal articles written in English. This condition makes English language proficiency a crucial competency in modern education. This study used a mixed-methods research design, integrating quantitative and qualitative approaches to gain a comprehensive understanding of students' motivation and language attitudes toward learning English. The results showed that students demonstrated a high level of motivation in learning English, with instrumental motivation emerging as the dominant orientation. Students were primarily motivated by practical and future-oriented goals, including global mobility, educational advancement, knowledge acquisition, and social recognition.